The Effects of Monetary Policy on The Euro Stock Market - Kassama, Alhassan (2022)
This paper analyses the level of impact that the European Central Bank’s (ECB) policy rates decided on by the Governing Council affects the European Stock market. We use the Stoxx Europe 600 index’s daily return data to represent in general, the aggregate European stocks. Our choice of daily frequency data is as a result of evidence of an endogeneity problem between the stock returns movement and the Central Bank’s policy rate decisions because monetary policy can also react to stock market developments. We adopt the event-study approach to address our hypotheses and use the Euro Overnight Index Average (EONIA) to measure the monetary policy rates in the conventional period which ends officially on the last conventional policy date before the first unconventional monetary policy announcement i.e. 22nd August 2007 and construct our proxy for conventional monetary policy surprises. In the unconventional era, we utilize a different approach from previous studies like Bernanke & Kuttner (2005), by extracting the Portuguese, Italian, Greece and Spain government bond yield and using the spread between those four (cross sectional average) and the German 10 year bond as our proxy for unconventional surprise rate. We define the start of the unconventional period to be on the 22nd August 2007 based on the ECB’s first unconventional monetary policy announcement. Furthermore, we identify governing council meeting dates in our paper as ‘Eventdate’ and outside those days are identified as ‘Non-Eventdate’. Our results indicate that the larger influence of the monetary policy on stock returns is during the unconventional period than the conventional period when unconventional policies were utilized. And that there is a higher response in equity returns to monetary policy announcements during Governing Council announcement days than those days when there is no Governing Council announcement. This emphasizes the point that the effect is greater on policy announcement days than outside those days. Our results further confirms the hypothesis that the effects of monetary policy on the stock market is predominantly dependent on shocks/unanticipated monetary policy. Furthermore, our results also show that the policy impact is the same across the portfolios sorted based on sizes. The level of significance or lack thereof of the parameter estimates are fairly similar to each other across the different size panels. Finally, our results show that there was no indication that internal economic activity specifically the exchange rates within the EU influenced the movement of stock prices significantly.